Divine names on the spot (Leuven ; Paris ; Bristol, CT)
vii, 256 sayfa
Keywords: “Ancient Greek and Semitic languages resorted to a large range of words to name the divine. Gods and goddesses were called by a variety of names and combinations of onomastic attributes. This broad lexicon of names is characterised by plurality and a tendency to build on different sequences of names; therefore, the 'Mapping Ancient Polytheisms' project focuses on the process of naming the divine in order to better understand the ancient divine in terms of a plurality in the making. A fundamental rule for reading ancient divine names is to grasp them in their context - time and place, a ritual, the form of the discourse, a cultural milieu - a deity is usually named according to a specific situation. From Artemis Eulochia to al-Lat, al-'Uzza and Manat, from Melqart to “my rock“ in the biblical book of Psalms, this volume journeys between the sanctuary on Mount Gerizim and late antique magical practices, revisiting rituals, hymnic poetry, oaths of orators and philosophical prayers. While targeting different names in different contexts, the contributors draft theoretical propositions towards a dynamic approach of naming the divine in antiquity.” --